(untitled) (International Nexus Multidisciplinary Research Journal, 2025)
A SEMINAR TO SCHOOL OF POSTGRADUATE STUDIES DEPARTMENT OF BUSINESS ADMINISTRATION FACULTY OF MANAGEMENT SCIENCES IGNATIUS AJURU UNIVERSITY, PORTHARCOUT, RIVER STATE LECTURER: DR. NICHOLAS A. ONYIA ABSTRACT This study conducts a comparative analysis of the impact of pre-inflation and post-inflation periods on the promotion strategies and customer retention of Nigeria Breweries Plc. Inflation significantly influences consumer behavior and marketing approaches, especially in Nigeria’s volatile economic environment. During pre-inflation periods, firms tend to adopt aggressive promotional tactics to attract and retain customers, leveraging higher disposable incomes. Conversely, post-inflation periods necessitate more value-focused promotions as consumers become more price-sensitive. Using a managers opinion survey method approach, including qualitative interviews and quantitative analysis of sales and promotional data, this research examines how Nigeria Breweries Plc adapts its marketing mix across these economic phases. The findings reveal that promotion strategies significantly differ between pre- and post-inflation periods and that these differences directly affect customer loyalty and retention. The study highlights the importance of strategic flexibility in marketing and offers practical insights for managers to develop resilient promotion plans that sustain customer relationships during economic fluctuations. This research contributes to the broader understanding of marketing adaptation in emerging economies and underscores the critical role of tailored promotional practices in ensuring long-term business viability amid macroeconomic instability.